TMIC-42. LEVERAGING B CELL IMMUNITY TO PROMOTE IMMUNOTHERAPY IN GLIOBLASTOMA. (14th November 2022) - Hou, David; Castro, Brandyn; Zolp, Andrew; Dapash, Mark; Arrieta, Victor; Zhao, Junfei; Zhang, Peng; Rashidi, Aida; Burnham, Emma; Patel, Ronit; Lesniak, Maciej; Miska, Jason; et al.
Abstract: Immunotherapy has revolutionized cancer treatment but has yet to be translated into brain tumors. Studies in melanoma and sarcoma, amongst other models, have revealed the accumulation of germinal-center-like B cells as a key survival predictor post-PD1 blockade. We seek to leverage B cell immunity to enhance immunotherapy effectiveness in glioblastoma (GBM). In human GBM and murine glioma models, we found that B cells in the tumor microenvironment (TME) are activated, but the expression of co-inhibitory molecules such as CD32 and CD72 blocks downstream effector function. Transcriptomic analysis showed high expression of inhibitory TGFβ receptors on B cells and high levels of TGFβ1 cytokine in the TME. We showed direct inhibition of B cell function through TGFβ signaling that could be prevented with TGFβ receptor blockade. Spatial multiplex immunofluorescence analysis of the TME revealed that tumor and myeloid cells express high levels of TGFβ and are also near B cells, allowing for TGFβ-mediated B cell inhibition. Blocking the TGFβ pathway via transgenic mice with TGFβ receptor knockout on B cells or TGFβ cytokine knockouts in myeloid cells, or generation of a CT2A tumor line with TGFβ cytokine knockdown, all demonstrated a survival benefit and more germinal-center-like B cells. There was also increased T cell proliferation and anti-tumor cytotoxicity. Finally, inhibiting αVβ8 integrin, a required factor that releases active TGFβ, is a translatable approach that also increased B cell proliferation and animal survival. Dual treatment with αVβ8+PD1 blockade showed the most potent survival as well as immunological memory against tumor re-challenge. Analysis of the B and T cell compartments after dual treatment showed synergy, with robust cellular proliferation and functional differentiation of plasmablasts and effector T cells. Collectively, our study highlights the importance of B cells in the TME and a remodeled approach to boost the effects of immunotherapy against GBM.